2007
DOI: 10.1096/fj.07-8213com
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor activation ameliorates type 1 diabetes

Abstract: Growing evidence indicates that adenosine receptors could be promising therapeutic targets in autoimmune diseases. Here we studied the role of adenosine receptors in controlling the course of type 1 diabetes. Diabetes in CD-1 mice was induced by multiple-low-dose-streptozotocin (MLDS) treatment and in nonobese diabetic (NOD) mice by cyclophosphamide injection. The nonselective adenosine receptor agonist 5'-N-ethylcarboxamidoadenosine (NECA) prevented diabetes development in both MLDS-challenged mice and in cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 38 publications
3
87
1
Order By: Relevance
“…This protection was associated with decreased pancreatic levels of Th1 cytokines, IL-12, TNF-a and IFN-g, and the chemokine MIP-1a (Nemeth et al 2007). Interestingly, using both specific receptor antagonists and transgenic knockout mice, the protection by adenosine against type I diabetes was found to be mediated through activation of the A 2b receptor subtype rather than the A 2a (Nemeth et al 2007), implicating both A 2a and A 2b receptor subtypes in adenosines modulation of the inflammatory system. The results obtained using adenosine and its receptor agonists in models of type I diabetes mimic those observed with both inosine and INO-2002, suggesting a role for A 2b receptor activation in inosine/INO-2002-mediated protection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This protection was associated with decreased pancreatic levels of Th1 cytokines, IL-12, TNF-a and IFN-g, and the chemokine MIP-1a (Nemeth et al 2007). Interestingly, using both specific receptor antagonists and transgenic knockout mice, the protection by adenosine against type I diabetes was found to be mediated through activation of the A 2b receptor subtype rather than the A 2a (Nemeth et al 2007), implicating both A 2a and A 2b receptor subtypes in adenosines modulation of the inflammatory system. The results obtained using adenosine and its receptor agonists in models of type I diabetes mimic those observed with both inosine and INO-2002, suggesting a role for A 2b receptor activation in inosine/INO-2002-mediated protection.…”
Section: Discussionmentioning
confidence: 97%
“…Activation of the adenosine A 2a receptor downregulates inflammation and protect against tissue damage (Ohta & Sitkovsky 2001) and inosine's inhibitory effect on inflammatory cytokine production is mediated in part by activation of this adenosine receptor (Hasko et al 2000). Recently, we have demonstrated that adenosine receptor activation ameliorates type I diabetes, as adenosine-5 0 -N-ethylcarboxanide (NECA), a non-selective adenosine receptor agonist, protects against MLDS-and cyclophosphamide-induced diabetes in NOD mice (Nemeth et al 2007). This protection was associated with decreased pancreatic levels of Th1 cytokines, IL-12, TNF-a and IFN-g, and the chemokine MIP-1a (Nemeth et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports indicated that CD39, the ectoenzyme mediating the conversion from ATP to adenosine on the cell surface, may be used by Tregs to regulate adenosine levels and, thus, exert their suppressive effects on other T cells (4,5). With respect to T1D, Haskó's group (29) reported several years ago that in drug-induced T1D (in CD-1 mice), A2BR signaling inhibited diabetogenesis. That report established a role for adenosine signaling in T1D and set the groundwork for our work.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a potent endogenous antiinflammatory and immunosuppressive molecule that is released from cells into the extracellular space at sites of inflammation and tissue injury (Németh et al, 2007). One key enzyme that has an important biological role in the metabolism of purine nucleosides is Adenosine deaminase (ADA), which catalyzes irreversible hydrolytic deamination of adenosine into inosine (Uz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%